A centralized automated-dispensing system in a French teaching hospital: return on investment and quality improvement. (11th July 2018) - Berdot, Sarah; Korb-Savoldelli, Virginie; Jaccoulet, Emmanuel; Zaugg, Vincent; Prognon, Patrice; Lê, Laetitia Minh Maï; Sabatier, Brigitte
Abstract: Objectives: To evaluate the return on investment (ROI) and quality improvement after implementation of a centralized automated-dispensing system after 8 years of use. Design: Prospective evaluation of ROI; before and after study to evaluate dispensing errors; user satisfaction questionnaire after 8 years of use. Setting: The study was conducted at a French teaching hospital in the pharmacy department, which is equipped with decentralized automated medication cabinets in the wards. Participants: Pharmacy staff (technicians and residents). Intervention(s): Implementation of a centralized automated-dispensing robot. Main Outcome Measure(s): The true ROI was prospectively and annually compared to estimated returns calculated after implementation and upgrade of the robot; dispensing errors determined by observation of global deliveries and the satisfaction of users based on a validated questionnaire were evaluated. Results: Following the upgrade, we found little difference for the ROI (+1.86%). The payback period increased by almost 3 years. There was a significant reduction of dispensing errors, from 2.9% to 1.7% ( P < 0.001). User satisfaction of the robot by the pharmacy staff was reported (score of 5.52 ± 1.20 out of 7). Conclusions: These systems are worthwhile investments and largely contribute to improving the quality and safety of the medication process.